A Standardized, Pragmatic Approach to Knee Ultrasound for Clinical Research in Osteoarthritis: The Johnston County Osteoarthritis Project. Issue 7 (29th June 2020) - Yerich, Nadiya V.; Alvarez, Carolina; Schwartz, Todd A.; Savage‐Guin, Serena; Renner, Jordan B.; Bakewell, Catherine J.; Kohler, Minna J.; Lin, Janice; Samuels, Jonathan; Nelson, Amanda E.
Abstract : Objective: This study sought to develop and employ a comprehensive and standardized ultrasound (US) protocol and scoring atlas for the evaluation of features relevant to knee osteoarthritis (KOA) in a community‐based cohort in the United States, with the goals of demonstrating feasibility, reliability, and validity. Methods: We utilized data from the fourth follow‐up (2016‐2018) of the Johnston County OA Project, which includes individuals with (~50%) and without radiographic KOA. All participants underwent standardized knee radiography and completed standard questionnaires including the Knee Injury and Osteoarthritis Outcome Score (KOOS). Bilateral knee US images were obtained by a trained sonographer using a standardized protocol and scored by trained rheumatologists using an atlas developed for this study. A total of 396 knees were each scored by two readers according to the atlas. Associations between US features, radiographic findings (graded by an expert radiologist), and KOOS scores were assessed. Results: Overall interreader reliability for US scoring was fair to moderate. The strongest correlations between US and radiographic features were seen for osteophytes, and similarly strong correlations were seen between US osteophytes and overall radiographic Kellgren‐Lawrence Grade, demonstrating criterion validity. Features of effusion/synovitis and osteophytes were most associated with KOOS pain and impaired function. Conclusion: US is a feasible, reliable, and valid method to assess features relevant to KOA in clinical and research settings. The protocol and atlas developed in this study can be utilized to evaluate KOA in a standardized fashion in future clinical studies, enabling greater utilization of this valuable modality in osteoarthritis.